Corporate social responsibility and financial performance: Do group affiliation and mandatory corporate social responsibility norms matter? - Siddhartha Barman; Jitendra Mahakud (IIMB Management Review, 2024)
This study examines the impact of corporate social responsibility (CSR) expenditure on the corporate performance of listed firms in India. It tries to explore the effect of business group affiliation and mandatory CSR norm on the CSR-performance relationship. The study period ranges from 2016 to 2021, and the data set comprises companies listed on the National Stock Exchange India. It employs a dynamic panel data model, and more specifically the system generalised method of moments technique to examine this issue. The results reveal a significant and positive association between CSR expenditure and corporate performance. It also shows that business group affiliation reduces CSR-performance sensitivity. Further, we find that mandatory CSR norms significantly influence the CSR-performance relationship.